2008
DOI: 10.1088/0004-6256/135/2/631
|View full text |Cite
|
Sign up to set email alerts
|

The Extinction Toward the Galactic Bulge From Rr Lyrae Stars

Abstract: We present mean reddenings toward 3525 RR0 Lyrae stars from the Galactic bulge fields of the MACHO Survey. These reddenings are determined using the color at minimum V -band light of the RR0 Lyrae stars themselves and are found to be in general agreement with extinction estimates at the same location obtained from other methods. Using 3256 stars located in the Galactic Bulge, we derive the selective extinction coefficientThis value is what is expected for a standard extinction law with R V,BV = 3.1 ± 0.3.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 37 publications
0
52
1
Order By: Relevance
“…A Gaussian fit to the (J − K s ) color distribution is then used to determine the mean color of the red clump. (Sumi 2004;Kunder et al 2008;Zoccali et al 2008), we obtain a dereddened mean color of (J − K s ) 0 = 0.68 for the RC stars in this region. We use this value as a reference for the intrinsic mean color of the RC, and its difference with respect to the measured RC color in any other region is an indicator of the extinction, given by E(J − K s ).…”
Section: Mean Color Of the Galactic Bulge Red Clumpmentioning
confidence: 69%
See 1 more Smart Citation
“…A Gaussian fit to the (J − K s ) color distribution is then used to determine the mean color of the red clump. (Sumi 2004;Kunder et al 2008;Zoccali et al 2008), we obtain a dereddened mean color of (J − K s ) 0 = 0.68 for the RC stars in this region. We use this value as a reference for the intrinsic mean color of the RC, and its difference with respect to the measured RC color in any other region is an indicator of the extinction, given by E(J − K s ).…”
Section: Mean Color Of the Galactic Bulge Red Clumpmentioning
confidence: 69%
“…Other important extinction maps are available with a partial coverage of the GB such as those of Kunder et al (2008) and Sumi (2004). However, for detailed studies of the GB, a high resolution and homogeneous extinction map covering the complete area of interest is missing.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of RR Lyrae in the bulge from Kunder et al (2008), variations with respect to the standard reddening law were observed in a few directions. However, they conclude that, on average, the extinction law of • , 30…”
Section: Discussionmentioning
confidence: 99%
“…This class of variable stars was used to characterize various components of the Milky Way, including the halo (Vivas & Zinn 2006;Helmi 2008;Miceli et al 2008;Helmi et al 2011;Drake et al 2014, etc. ), the bulge (Alcock et al 2000;Kunder et al 2008;Dékány et al 2013;Pietrukowicz et al 2015;Gran et al 2016, etc. ), the Solar neighborhood (Layden 1994(Layden , 1998, and the outer thick disk toward the anticenter (Sesar et al 2013).…”
Section: Introductionmentioning
confidence: 99%